Inklusifitas Keuangan Syariah dan Kemiskinan di Indonesia - Iskandar, Azwar; Possumah, Bayu Taufiq (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2018)
This paper aims at calculating and analyzing the Index of Syariah Financial Inclusion (ISFI) during the period of 2015-2018 and its correlation with poverty level in Indonesia. Using the secondary data of 33 provinces in Indonesia from Badan Pusat Statistik (BPS), Bank Indonesia and Otoritas Jasa Keuangan (OJK) and Index of Financial Inclusion (IFI) method, this paper found that the Index of Syariah Financial Inclusion is generally low and DKI Jakarta is the most financially inclusive province of Indonesia. Furthermore, the results show that the Index of Syariah Financial Inclusion is negatively correlated with the poverty level. This conclusion suggests the promotion of Syariah Financial Inclusion to be a policy priority in Indonesia to achieve the central goals of inclusive growth, welfare and economic development.